Monolith experiment in Vilnius: between idea and pragmatism - Ruseckaitė, Indrė; Černauskienė, Aušra (Journal of Architecture and Urbanism, 2012)
In postwar development of modernist architecture, ambiguity of reinforced concrete in the role of a causer of a qualitative leap of the architectural thought is particularly reflected by controversial application directions and scales of the present material: from industrialised mass construction of prefabricated reinforced concrete large-panel houses seen as pure pragmatism to individual examples of monolithic reinforced concrete architecture with exclusive plasticity seen as idea disseminators. This is the relation between the ideological content and pragmatism of the monolithic reinforced concrete technology the present article deals with discussing the issue in the contexts of Vilnius housing construction. Multi-dwelling units of monolithic reinforced concrete constructed in compliance with an innovative and experimental technology of that time have been chosen due to relatively low realisation scale thereof and due to the fact that the experiment under investigation hardly took a couple of the last decades of the Soviet era, the end whereof also denotes breakup of the phenomenon. The paper aims at answering what are the pragmatic and ideological impulses having determined development of the technology, what architectural and urban ideas are displayed by the buildings constructed; why the monolithic experiment with the significant role to be played in the unrealised perspective plans of urban development has finished together with the Soviet period and what are today's manifestations with respect to assessment and architectural interpretations of the phenomenon. Conclusions of the article maintain that the best display of the relation between the ideological content and pragmatism of the monolithic reinforced concrete technology in Vilnius is exposed in the contexts of housing construction. Demand for the rapid and inexpensive housing construction technology and new reinforced concrete technologies were combined in the field of construction industrialisation and projects of multiple apartment houses. Necessity for original non-standard architectural vertical accents in the monotonous environment characteristic of the quarters of standard apartment houses encouraged to search for an appropriate innovative technology. Monolithic reinforced concrete (as an alternative to prefabricated reinforced concrete large-panel or brickwork construction being unfavourable to the present typology) was chosen due to a range of pragmatic reasons such as comparatively short design and realisation time, lower labour expenditures and less metal input required.Having joined together ideological and pragmatic needs, the monolithic reinforced concrete technology was applied for some ninety apartment houses in Vilnius from 1974 to 1990. Initially employed for the ultimate challenges, i.e. tower-blocks, later the monolithic experiment was used in construction of barrier blocks and terraced houses of composite structures, whereas at the end of the Soviet era it was utilised for construction of single-family houses. Greater technological potential of the experiment having lasted just for eighteen years enabled more freedom in interpretation of the plan structure of an apartment house, therefore, innovations in living spaces are an integral part of the monolithic experiment. Sculpturesqueness of monolithic towers, form iconicity, demonstration of functional building segments in the plan and volume point to ideological changes in modernist architecture. Switchover from one form to structural combination of a few ones, display of the present structurality in the volume also suggest reflections of structural ideas of "spatial blocks" in design of apartment houses, wherein a flat or a group of flats turn into a segment or block of the plan and spatial structure. Being able to open a range of opportunities for exposition of monolithic reinforced concrete and texture thereof, thereby ensuring development of the "techno-functional" structuralism trend, the monolithic reinforced concrete technology failed to gain the expected scope in the real life due to limited technological possibilities.Contextual ideas, born in the sixties of the 20th c. and declaring the necessity to reinterpret the principles of historic architecture and the old city forms as well as to adapt them to the newly developed urban areas, are also found in the changes of Lithuanian architectural and urban thought. The notion of architectural mounds of Vilnius generated during this period was both elaborated in the central part of the city and rephrased in residential districts. Monolithic tower-blocks were clustered next to the major (micro)raion centres, thereby forming mounds, or were used as peaks of the mounds shaped of standard apartment houses, often turning into the functional concentration points of microraions themselves. At that time, the idea of a barrier block acting as a protection wall that safeguards the microraion against highway noise was developed, however, it was worked out just on the basis of the monolithic technology. Demand for the morphotype with respect to switchover from free building-up to perimeter one and possibilities thereof are marked by construction of perimeter blocks of apartment complexes, the ideas of "privacy" reborn wherein were eventually transformed in projects of monolithic terraced and individual houses as well as in very few realisations.Monolithic reinforced concrete apartment houses represent the technological heritage of the uncompleted and discontinued monolithic experiment having gone out together with the Soviet era. Non-relevant scopes of apartment house construction with the scale of that time as well as the doubts having arisen at the end of the Soviet period with respect to justification of the monolithic technology in construction of apartment houses testify to the end of the monolithic experiment under discussion. Application field of monolithic reinforced concrete moves to interior building structures "dressing" the exterior with modern materials, therefore, monolithic facades just remain a part of the experiment of the past Soviet era, the reverberations whereof are found in individual buildings of today's architecture solely.Article in Lithuanian.Monolito eksperimentas Vilniuje: tarp idėjos ir pragmatiškumoSantrauka. Gelžbetonio kaip kokybinio architektūrinės minties šuolio kaltininko dviprasmiškumas pokarinėje modernistinės architektūros raidoje ypač matomas iš kontraversiškų šios medžiagos naudojimo krypčių ir mastų: nuo industrializuotos masinės surenkamų gelžbetoninių stambiaplokščių namų statybos kaip grynojo pragmatiškumo iki pavienių išskirtinės plastikos monolitinio gelžbetonio architektūros pavyzdžių kaip idėjos skleidėjų. Būtent monolitinio gelžbetonio technologijos idėjiškumo ir pragmatiškumo santykis straipsnyje ir nagrinėjamas, šį klausimą perkėlus į Vilniaus gyvenamosios statybos kontekstus. Monolitinio gelžbetonio gyvenamieji namai, pastatyti naudojant savo laiku inovatyvią ir eksperimentinę technologiją, pasirinkti dėl palyginti nedidelio jų įgyvendinimo masto ir dėl to, kad šis eksperimentas tetruko ne visus porą paskutinių sovietinės eros, kurios pabaiga žymi ir šio fenomeno nutrūkimą, dešimtmečių. Tekste siekiama atsakyti, kokie pragmatiniai ir idėjiniai postūmiai lėmė šios technologijos plėtojimą, kokios architektūrinės ir urbanistinės idėjos skleidžiasi šiuose objektuose; kodėl monolitinis eksperimentas, kuriam nemenkas vaidmuo numatytas neįvykusiuose miesto plėtros ateities planuose, pasibaigė kartu su sovietmečiu ir kaip reiškiasi šiandieniniai šio reiškinio vertinimai bei architektūrinės interpretacijos.Reikšminiai žodžiai: sovietmečio architektūra, monolitinis gelžbetonis, sovietmečio gyvenamieji rajonai, daugiabučių namų tipologija.